Spinal astrocyte-derived interleukin-17A promotes pain hypersensitivity in bone cancer mice - Huizhu Liu; Xuejing Lv; Xin Zhao; Lanxing Yi; Ning Lv; Wendong Xu; Yuqiu Zhang (Acta Pharmaceutica Sinica B, 2024)
Spinal microglia and astrocytes are both involved in neuropathic and inflammatory pain, which may display sexual dimorphism. Here, we demonstrate that the sustained activation of spinal astrocytes and astrocyte-derived interleukin (IL)-17A promotes the progression of mouse bone cancer pain without sex differences. Chemogenetic or pharmacological inhibition of spinal astrocytes effectively ameliorates bone cancer-induced pain-like behaviors. In contrast, chemogenetic or optogenetic activation of spinal astrocytes triggers pain hypersensitivity, implying that bone cancer-induced astrocytic activation is involved in the development of bone cancer pain. IL-17A expression predominantly in spinal astrocytes, whereas its receptor IL-17 receptor A (IL-17RA) was mainly detected in neurons expressing VGLUT2 and PAX2, and a few in astrocytes expressing GFAP. Specific knockdown of IL-17A in spinal astrocytes blocked and delayed the development of bone cancer pain. IL-17A overexpression in spinal astrocytes directly induced thermal hyperalgesia and mechanical allodynia, which could be rescued by CaMKIIα inhibitor. Moreover, selective knockdown IL-17RA in spinal Vglut2+ or Vgat+neurons, but not in astrocytes, significantly blocked the bone cancer-induced hyperalgesia. Together, our findings provide evidence for the crucial role of sex-independent astrocytic signaling in bone cancer pain. Targeting spinal astrocytes and IL-17A/IL-17RA-CaMKIIα signaling may offer new gender-inclusive therapeutic strategies for managing bone cancer pain.